Five Years After : European Union Membership and Macro-Financial Stability in the New Member States - Cihak, Martin (IMF Working Papers; Working Paper, 2009)
The proximity of the European Union, the prospect of membership, and actual entry by the New Member States (NMS) increased economic and financial integration in the region, leading to fast economic growth based on sizeable capital inflows. EU membership helped in developing sound macroeconomic and financial stability frameworks in the NMS. However, these frameworks remain work in progress and as such could not safeguard against private sector exuberance or risky policies, especially in the face of an unprecedented global financial crisis. Hence, more prudent policies and further strengthening of policy frameworks, especially with respect to financial stability, seem warranted.